INTONATION STRUCTURE OF ENGLISH - Muzaffarova Sevinch; Sattorova Sabohat; Husniddinova Ozoda (TADQIQOTLAR, 2025)
Abstract This article explores the structure of intonation in English and its significance in effective communication. It highlights key features of intonation, such as pitch variation, stress, emphasis, and boundary tones, demonstrating how these elements contribute to meaning and emotional expression. The article emphasizes the importance of mastering intonation to improve fluency and listening skills. It also discusses how intonation patterns can vary across cultures and regions and suggests methods for improving intonation through consistent practice and exposure to authentic English. Overall, the article provides insights into the complexity of intonation and its role in English communication.